2015
DOI: 10.1007/s10459-015-9638-5
|View full text |Cite
|
Sign up to set email alerts
|

Can student self-ratings be compared with peer ratings? A study of measurement invariance of multisource feedback

Abstract: Measurement invariance is a prerequisite for comparing measurement scores from different groups. In medical education, multi-source feedback (MSF) is utilized to assess core competencies, including the professionalism. However, little attention has been paid to the measurement invariance of assessment instruments; that is, whether an instrument holds the same meaning across different rater groups. To examine the measurement invariance of the National Taiwan University professionalism MSF (NTU P-MSF) in order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 54 publications
1
13
0
1
Order By: Relevance
“…Like others have reported, 25 SA and PA correlated with each other generally as well as at the level of their subdomains in our study also. Interestingly, both SA and PA ratings are much higher than ESA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Like others have reported, 25 SA and PA correlated with each other generally as well as at the level of their subdomains in our study also. Interestingly, both SA and PA ratings are much higher than ESA.…”
Section: Discussionsupporting
confidence: 91%
“…This continuity can be included into students’ portfolios; in a similar manner to ‘multisource feedback’ discussed by others. 25 This study incites fresh excitation in an old discussion. Simplified subjective tools need repeated adaptation, validation, reliability check and evaluation based on the needs and settings of a course, and students’ level.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the OSCE helped increase the NNPs' con dence and reduce their personal embarrassment when encountering similar clinical situations. Previous reports showed that nursing students found that the OSCE help them deal with stressful clinical situations and develop their con dence in clinical practice [24][25][26][27]. Student midwives saw the OSCE as a valid means of assessment and that it increased their con dence in performing clinical skills [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Para além disso, este estudo estabelece evidências importantes sobre a invariância do ITEA. Embora a invariância de medição seja um pré-requisito para a realização de comparações entre grupos, raramente é testada (Lee, Tsai, Chiu, & Ho, 2016). Assim, a falta de variação do ITEA entre os papéis parentais, bem como entre o género dos participantes, sugere uma evidência importante para a robustez dessa medida de avaliação do processo de individuação aos pais em jovens adultos.…”
Section: Discussionunclassified